Digitalisasi Sekolah Melalui Pengembangan Website dan Layanan Sekolah Berbasis Teknologi Informasi - Murhadi Murhadi; Ponidi Poni (Universitas Muhammadiyah Purworejo, 2019)
Schools as a place to forge students to become people who are ready to welcome the 21st century. 21st Century projection factors indicate the ability of literacy, one of which is technology literacy. Schools are required to familiarize students with the application of information technology. The method that can be applied is by digitizing the School. SMPN 4 Pakem has begun digitizing education with various steps and efforts. So it is necessary to study the digitization process and its impact on increasing existing resources. The method used in this paper is through several stages. The initial stage is observation, which aims to see the activeness of the parts that have been digitalized. SMPN 4 Pakem implements education digitization through several sections, namely website, library, and evaluation and assessment system. The SMPN 4 Pakem website has become a medium of communication and information sources both internal and external. SMPN 4 Pakem Library implements library automation to improve services to users with the help of information technology-based applications.